Inactivation of Listeria monocytogenes and Salmonella Typhimurium in beef broth and on diced beef using an ultraviolet light emitting diode (UV-LED) system. (15th March 2022) - McSharry, Siobhán; Koolman, Leonard; Whyte, Paul; Bolton, Declan
Abstract: Ultraviolet Light-Emitting Diode (UV-LED) is a potential decontamination technology for reducing bacterial loads on meat. This study investigated the efficacy of UV-LED technology to reduce Listeria monocytogenes, Salmonella Typhimurium, total viable counts (mesophiles (TVCm) and psychrophiles (TVCp)) and total Enterobacteriaceae counts (TEC) when suspended in beef broth and after inoculation onto diced beef. Inoculated samples (10 7  CFU/mL) were treated with UV light using single (255, 265, 285 nm) and combined (255 and 265 nm, 255 and 285 nm, 265 and 285 nm) wavelengths, exposed for 2, 30 or 60 min. Significant ( p < 0.05 ) reductions in all of the target bacteria were achieved after 2 min with almost complete elimination after 60 min for all the individual and combinations of wavelengths tested, with the exception of 255 nm. On the diced beef, significant ( p < 0.05 ) reductions in L. monocytogenes, TVCm and TEC were achieved using 285 nm and all of the combined wavelength treatments after 60 min. It was concluded that UV-LED technologies have potential application for the decontamination of beef products and validation in a commercial plant should be undertaken to facilitate the transfer of this technology to the meat sector. Highlights: UV-LED significantly reduced L. monocytogenes in beef broth and on diced beef. S. Typhimuirum were also significantly ( p  < 0.05) reduced in beef broth. The most effective single UV wavelength treatment was 285 nm. Wavelength 285 nm combined with 255 nm or 265 nm enhance bactericidal inactivation.